دراسة اقتصادية لمنظومة كهربائية بالخلايا الكهرشمسية لأهداف زراعية في المناطق الشرقية لسورية - صبيح مسعود (Latakia University Journal -Engineering Sciences Series, 2019)
يتضمن هذا البحث دراسة حسابية يمكن تطبيقها على أرض الواقع بهدف استخدام مجمعات الخلايا الكهرشمسية للحصول على الطاقة الكهربائية اللازمة لتغذية الأحمال المطلوبة من أجل سقاية أراضي زراعية بمساحة 4047 [Hectare] تقع في المنطقة الشرقية لسورية وتحديدا في منطقة المالكية الواقعة إلى الشرق من مدينة القامشلي. بالإضافة الى تغذية أحمال أخرى ممثلة بأنشطة حياتية يومية يقوم بها المزارعون وأسرهم والبالغ عددهم خمسة آلاف نسمة والذين يسكنون في قرية نموذجية ضمن المساحة المدروسة. تضمن هذا البحث آلية عمل مستقرة للنظام باستخدام مولدات طاقة بديلة عند غياب الإشعاع الشمسي ممثلة بالمدخرات الحمضية. في البداية تم حساب كمية المياه اللازمة للسقاية بطريقتي الري بالتنقيط والري بالرذاذ. الخطوة التالية كانت الدراسة التحليلية لمختلف الأحمال الكهربائية وتحديد متوسط القدرة اليومية للأحمال المطلوبة. قدم هذا البحث أيضا الدراسة الفنية لمجمعات الخلايا الكهرشمسية والمدخرات والحسابات الهندسية لها اعتمادا على بيانات الإشعاع الشمسي وزمن السطوع الشمسي للمنطقة المدروسة وربطها مع حجم الحمولة. شمل البحث أيضا دراسة اقتصادية تم التعرض من خلالها لحساب الكلفة الثابتة أو كلفة الإنشاء لمكونات منظومة العمل، حساب الكلفة المتغيرة، حساب الكلفة السنوية ومن ثم تقدير كلفة إنتاج الكيلووات الساعي لإبراز الأهمية الاقتصادية لاستخدام الطاقة الشمسية في المواقع الريفية والزراعية المعزولة على السواء. This research involves an applied study to be executed on the lands using complex of Solar Cells to get the needed energy to feed the required loads for irrigating the agricultural lands of 4047 Hectares located in the Eastern Syrian Area specifically the Malkieh district located to the east of Kamishli city. It can also used to feed the loads of other daily activities conducted by the farmers and their families of five thousands people living in a typical village within the studied area. This study involves the mechanism of steady work of the system using energy generators as a substitute at the absence of solar radiation represented with the lead-acid batteries. At the beginning computing the quantity of needed water for irrigation is done by means of drip irrigation and sparkling. The next step is the analytic study of different electrical loads and determining the average daily energy of the required loads. The research has also rendered the technical study of the solar cell complex and batteries as well as the engineering computation relying on the data of the solar radiation and the sun shine duration of the studied zones linking them with the size of loads. The implemented step has involved the economical study which came across through the fixed cost computation or the structural of the components of the work system, computing the running cost, the annual cost and then estimating the production cost of Kilowatt-hour by stressing to the economical importance using the solar energy in the isolated areas in the rural location and agricultural altogether.